Attention to Human Dignity and Its Role in Increasing Spirituality - Ahmady, Sameer Ahmad; Ebrahimi, Mohammad Yunus; Safi, Shahidullah (Integrated Journal for Research in Arts and Humanities, 2023)
The main purpose of this paper is to investigate about the dignity of human and its role in increasing the spirituality in light of Islam. The founding shows that spirituality has been considered as a desirable thing throughout humans’ life and lots of effort have been made to strengthen it. There are several factors that raise and cultivate spirituality, but among these factors, human dignity has essential role and basis. In this research, while explaining the concept of spirituality, the importance of human dignity in creating a spiritual personality is emphasized, and how the influence of human dignity in increasing spirituality will also be investigated, and it is proven that the source of spirituality is paying attention to inherent and deprivations, neglect and lack of attention to the position and dignity of the royal soul of man.